Megestrol acetate for appetite stimulation and weight gain in older adults with unintentional weight loss: a systematic review and meta-analysis - Larissa de Freitas do Lago-Abreu; Raphael Lopes Olegário; Luciana Lilian Louzada Martini; Einstein Francisco Camargos (Geriatrics, Gerontology and Aging)
Unintentional weight loss in older adults is linked to multiple factors, being most often associated with comorbidities such as cancer, dementia syndromes, chronic obstructive pulmonary disease, and chronic kidney disease. Difficulty in managing this condition can quickly lead to malnutrition and, consequently, a state of cachexia. There is a dearth of studies in the literature regarding pharmacotherapeutic interventions for this population, with megestrol acetate (MA) being the most commonly studied medication. In this systematic review, we evaluated the use of MA to improve appetite and treat unintentional weight loss and/or the anorexia-cachexia syndrome in older adults. Randomized studies published up to December 2023 in three languages (Portuguese, Spanish, or English) were retrieved from five databases. We included 25 studies, most of which addressed the use of MA for treatment of patients diagnosed with cancer and the anorexia-cachexia syndrome. We used the PEDro scale to assess methodological quality of the included studies and calculated measures of heterogeneity, such as the tau-squared (τ2), I-squared (I2), and Q test, to assess consistency across studies. Although the studies selected for the systematic review suggest that patients with the anorexia-cachexia syndrome secondary to cancer may benefit from MA therapy, a meta-analysis of 8 selected studies (total n = 592) did not confirm this effect (p = 0.104). The indication of MA for treatment of patients with weight loss required further studies with better methodological designs to evaluate the efficacy and safety profile of this medication in older adults. PROSPERO registry number CDR42024497640.